2020
DOI: 10.1177/1538574420940090
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Supervised Exercise Significantly Improves Walking Performances Without Changing Hemodynamic Parameters in Patients With Symptomatic Lower Extremity Peripheral Artery Disease

Abstract: We evaluated the outcome of multimodal supervised exercise training (SET) on walking performances and different hemodynamic parameters (ankle/toe-brachial index [ABI/TBI], and transcutaneous oxygen pressure [TcPO2]) in patients with symptomatic lower extremity peripheral artery disease (PAD). Whether hemodynamic parameters predict walking performances at baseline and following SET was also investigated. Fontaine stage II PAD’s patients following a 3-month SET were retrospectively included. Hemodynamic paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 35 publications
(50 reference statements)
1
18
0
Order By: Relevance
“…However, in our study, we observed that ABI was significantly increased at 6 months compared with the post SET values (mean difference: 0.06). In addition, as we already showed elsewhere [ 16 ], TBI increased significantly following SET (mean difference 0.04). Surprisingly, the values remained significantly higher at each following endpoint.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…However, in our study, we observed that ABI was significantly increased at 6 months compared with the post SET values (mean difference: 0.06). In addition, as we already showed elsewhere [ 16 ], TBI increased significantly following SET (mean difference 0.04). Surprisingly, the values remained significantly higher at each following endpoint.…”
Section: Discussionsupporting
confidence: 83%
“…Past studies have abundantly proved the effectiveness of SET on walking performance in patients with claudication [ 8 , 11 , 12 , 13 , 16 , 22 , 23 , 24 ]. In agreement with these studies, our results show an improvement in walking capacities assessed by PFWD, MWD, and by 6MWD after a 3-month SET.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Angiofit study is a longitudinal observational cohort of symptomatic patients (Fontaine stage II) participating in multimodal SET with stable uni- or bilateral lower limb claudication and resting ankle-brachial index (ABI) ≤ 0.9 or decreased post-exercise ABI > 20%. We recently showed that our clinical multimodal SET is effective in improving walking performance and quality of life [ 18 , 19 , 20 ] and that these improvements are maintained up to 12 months follow-up in patients with symptomatic PAD [ 20 ]. Compared to these previous observations [ 18 , 19 , 20 ], in the present study we included all patients participating in our clinical SET program up to 2020, having performed walking tests (treadmill and 6 min) and self-perceived HRQoL questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…We recently showed that our clinical multimodal SET is effective in improving walking performance and quality of life [ 18 , 19 , 20 ] and that these improvements are maintained up to 12 months follow-up in patients with symptomatic PAD [ 20 ]. Compared to these previous observations [ 18 , 19 , 20 ], in the present study we included all patients participating in our clinical SET program up to 2020, having performed walking tests (treadmill and 6 min) and self-perceived HRQoL questionnaire. Exclusion criteria are inability to participate in SET three times weekly, critical limb ischemia, and cardiac contraindication to exercise.…”
Section: Methodsmentioning
confidence: 99%